(untitled) (Archives of Clinical Psychiatry, 2015)
Background Telemental Health Care has reported very good results and is included within mental health priorities by the World Health Organization. Objective To provide an overview of the current situation of the integration of Brazilian telemedicine activities into primary health care. Methods Critical review based on MEDLINE database, using the keywords “telemedicine”, “primary health care” “mental health” and “telemental health”, on websites of the Brazilian Ministry of Health and Brazilian Telehealth Network Program, and on personal communication. Results The Brazilian Telehealth Network Program is well positioned and connects primary health care with academic centers. Regulations standards allow a broader scope of activities for psychologists, however, are more restrictive for physicians. In Brazil most of telemental health activities are focused on education and second opinion consulting. A huge challenge must be overcome considering the regional differences and the telehealth implementation experience. Research initiatives have been initiated both in the implementation and evaluation of the mental health assistance into primary health care. Discussion Brazilian Telemental Health initiatives into Primary Care are aligned with other examples around the world, have a great potential for improving mental health care service delivery, and access to proper mental health care, especially if articulated in a national program and coordinated research.